HÁBITOS DE HIGIENE Y SU INFLUENCIA EN EL DESARROLLO INTEGRAL DE LOS NIÑOS Y NIÑAS DE LA ESCUELA FISCAL MIXTA CARLOS BURNEO ARIAS, Y LA INTERVENCIÓN DE LA TRABAJADORA SOCIAL - Mayo Gonzàlez, Marìa Marisol (2015)
Personal hygiene is defined as the set of measures and standards to be fulfilled individually to achieve and maintain acceptable physical presence, and an adequate state of health is the basic concept of cleaning, grooming and pampering. The problem of poor hygiene affects the health of children so that they are vulnerable to disease, neglect their image being exposed to countless humiliations, and affecting their development. Therefore this research entitled "" hygiene habits and their influence on the overall development of the children of the Joint Public School Burneo Carlos Arias, and the intervention of the social worker "had as its overall objective to determine the causes and consequences of inadequate practice of personal hygiene in girls / os of the Joint Public School Burneo Carlos Arias. The specific objectives were theoretically substantiate the categories that expand knowledge about hygiene habits, also conceptualized the categories on the issue, investigate causes and consequences that entails inadequate practice and finally present an alternative proposal to strengthen the practice of habits personal hygiene. Major findings in this investigation began with the lack of involvement of the family in instilling hygiene, making an impact on their development, and the data were limited participation of teachers in making educational programs promoting personal hygiene.